Las nuevas formas de migración como efecto de la precarización de políticas de Estado (2022)
The purpose of this essay is to show how, as a result of the precariousness of State policies and processes of exclusion that operate in society, the migratory phenomenon, in accordance with its relationship with the experience and combined with the daily emergency in their places of origin, has been transformed in recent years into a state of vulnerability and fragility. Thus, new aesthetic and political reshaping have emerged that, sponsored by exacerbated global economies, reorient the migrants’ condition as human beings to one of “life in transit” that reifies them as perishable beings and propitious, in that state of invisibility, to strengthen the logics of cruelty and violence for their criminalization, use, expropriation and disposal in illegal post-global markets. This reflection seeks, from an empirical-analytical approach, to propose a reorientation around the recognition of the migratory phenomenon as dignified lives in transit, through which new visions of human rights can be rearticulated from the institutions of the State to make migration a condition of inclusive possibility that corresponds to the recognition of a “dignified life” hand in hand with hospitable policies of the States.